A population-based study on health and living conditions in areas with mixed Sami and Norwegian settlements – the SAMINOR 2 questionnaire study - Brustad, Magritt (Co-Action Publishing, 2014)
OBJECTIVES: To describe the method, data collection procedure and participation in The Population-based Study on Health and Living Conditions in Areas with both Sami and Norwegian Settlements – the SAMINOR 2 questionnaire study. STUDY DESIGN: Cross-sectional and semi-longitudinal. METHODS: In 2012, all inhabitants aged 18–69 and living in selected municipalities with both Sami and Norwegian settlements in Mid and Northern Norway were posted an invitation to participate in a questionnaire survey covering several topics related to health and living conditions. The geographical area was similar to the area where the SAMINOR 1 study was conducted in 2003/2004 with the exception of one additional municipality. Participants could alternatively use a web-based questionnaire with identical question and answer categories as the posted paper version. RESULTS: In total, 11,600 (27%) participated (16% used the web-based questionnaire), with a higher participation rate among those over 50 (37% for women and 32% for men). Some geographical variation in participation rates was found. In addition, for those invited who also participated in the SAMINOR 1 study, we found that the participation rates increased with the level of education and income, while there was little difference in participation rates across ethnic groups. CONCLUSION: The knowledge generated from future theme-specific research utilizing the SAMINOR 2 database has the potential to benefit the general population in this geographical area of Norway, and the Sami people in particular, by providing knowledge-based insight into the health and living conditions of the multi-ethnic population in these parts of Norway.